Pedagogical Facilitation In The Development Of The Subject Potential Of Future Masters - Gabdulbarovna Mukhametzyanova, Flera; Kazan Federal University, Institute of International Relations, History and Oriental Studies (2017)
The article presents the author's vision of the use of pedagogical facilitation in the development of the subject potential of future masters. The relevance of the possibility of using pedagogical facilitation in the preparation of future masters stated in the article is due to the fact that there is a new social and pedagogical phenomenon in the higher education in Russia - facilitation. The pedagogical facilitation in higher education is considered by us as "strengthening", increasing the productivity of education (teaching, upbringing, development) among the students as subjects of educational and professional activity. Pedagogical facilitation is a technology based on the use of a special style of communication by the university teacher in the context of the personality of teacher and student, based on the use of new ideas in the training group as a team to solve a particular problem. The main approach, based on the solution of this task, is the subject-oriented approach to the students of the university, which is necessary for the university teacher to create a facilitation situation for the student's development as a subject of educational and professional activity.